Multiscale modeling of the coupled electromechanical behavior of multifunctional nanocomposites. (15th January 2019) - Alian, A.R.; Meguid, S.A.
Graphical abstract: Abstract: In this first time effort, we developed a multiscale coupled electromechanical model capable of computing the piezoresistive properties of carbon nanotube (CNT)-reinforced composites. Monte-Carlo based algorithm was used to generate representative volume elements (RVEs) randomly filled with CNTs surrounded by the polymer matrix. The coupling between the applied mechanical load and the resulting electrical response was treated in a sequential manner in two steps. Firstly, a three-dimensional finite element model of the RVE was developed to determine the structural response of the nanocomposite system under different loading conditions. The results of the finite element model were then used to update the locations of the CNTs in the deformed RVE. Secondly, an electrical model based on the modified nodal analysis technique was developed to calculate the corresponding electrical conductivity of the nanocomposite. The developed model was successfully used to determine the piezoresistive behavior of CNT-epoxy composite under tension, compression, and shear loads. The results show that the composite gauge factor can reach up to 3.95 and is sensitive to the loading direction and CNT volume fraction. The predictions of the current model are in good agreement with the experimental findings of earlier studies, verifying its validity.